Eskimos mit Schneebrillen, vom Schneeschaufeln ausruhend, Okak 1911 - Bohlmann, Ernst, 1864-1945. (2001)
Photograph of a group of Inuit wearing snow goggles resting with their snow shovels at Okak mission station, 1911. Photograph of a group of Inuit wearing snow goggles resting with their snow shovels at Okak mission station, 1911.